Biotechnological Applications of Acetic Acid Bacteria - Raspor, Peter; Goranovi, Dušan (Critical reviews in biotechnology, 2008)
The acetic acid bacteria (AAB) have important roles in food and beverage production, as well as in the bioproduction of industrial chemicals. In recent years, there have been major advances in understanding their taxonomy, molecular biology, and physiology, and in methods for their isolation and identification. AAB are obligate aerobes that oxidize sugars, sugar alcohols, and ethanol with the production of acetic acid as the major end product. This special type of metabolism differentiates them from all other bacteria. Recently, the AAB taxonomy has been strongly rearranged as new techniques using 16S rRNA sequence analysis have been introduced. Currently, the AAB are classified in ten genera in the family Acetobacteriaceae. AAB can not only play a positive role in the production of selected foods and beverages, but they can also spoil other foods and beverages. AAB occur in sugar- and alcohol-enriched environments. The difficulty of cultivation of AAB on semisolid media in the past resulted in poor knowledge of the species present in industrial processes. The first step of acetic acid production is the conversion of ethanol from a carbohydrate carried out by yeasts, and the second step is the oxidation of ethanol to acetic acid carried out by AAB. Vinegar is traditionally the product of acetous fermentation of natural alcoholic substrates. Depending on the substrate, vinegars can be classified as fruit, starch, or spirit substrate vinegars. Although a variety of bacteria can produce acetic acid, mostly members of Acetobacter, Gluconacetobacter, and Gluconobacter are used commercially. Industrial vinegar manufacturing processes fall into three main categories: slow processes, quick processes, and submerged processes. AAB also play an important role in cocoa production, which represents a significant means of income for some countries. Microbial cellulose, produced by AAB, possesses some excellent physical properties and has potential for many applications. Other products of biotransformations by AAB or their enzymes include 2-keto-L-gulonic acid, which is used for the production of vitamin C; D-tagatose, which is used as a bulking agent in food and a noncalorific sweetener; and shikimate, which is a key intermediate for a large number of antibiotics. Recently, for the first time, a pathogenic acetic acid bacterium was described, representing the newest and tenth genus of AAB.